FORMATION OF THE ENTREPRENEURIAL SPIRIT OF PROSPECTIVE TEACHERS THROUGH PROJECT-BASED LEARNING - Adriyani, Zuanita; Malik, Muh Syauqi (Universitas Tanjungpura, 2022)
This research aims to find out whether the entrepreneurial spirit of prospective Madrasah Ibtidaiyah teachers can be formed with the application of project-based learning models. The type of research used in this study is descriptive quantitative research with sampling techniques in purposive sampling techniques. The sample population selected was Madrasah Ibtidaiyah Teacher Education UIN Walisongo Semarang semester IV class 2018/2019. The research sample used was class IV A, with 40 students. The free variable in this study is a project-based learning model as aloe vera hand sanitizer, young coconut rotary ice cream, jelly candy, dab soap, character's light sleeper, rainbow ice lolly, making salted eggs with onion flavor and rendang flavor, mosquito repellent candles, making BioLim, and manufacture of pandan-scented candlenut hair oil. In contrast, the tied variable is the student's entrepreneurial spirit. The conclusions showed the entrepreneurial spirit of prospective teachers through a project-based learning model in a suitable category with an average score of 14.1. The biserial correlation formula obtained a value of RB 0.54 and KD of 29.24%. The figure means that the project-based learning model is good enough to contribute to the formation of the entrepreneurial spirit of prospective teachers by 29.24%. Student response to the application of project-based learning models to foster the entrepreneurial spirit of future teachers gives a positive reaction with agreed categories. The average score is 3.6.